The Condition of the Couple's Agreement in Choosing Housing and the Guarantee of its Implementation - محمدمهدی hamidi (فقه و حقوق خانواده)
Choosing a suitable housing for cohabitation is considered one of the rights and duties of the man. However, it may be stipulated in an agreement during the contract or in a separate contract that the choice of home is delegated to the wife or that it is selected with the agreement and cooperation of the couple. If the couple has agreed to the condition for choosing housing, it is not clear whether, in the event of no agreement, this condition will be eliminated and the husband's leadership in unilaterally choosing housing will return, or, like any other binding contract, the court must be consulted for its implementation. In this regard, conflicting judicial opinions have also been issued, and some judges have believed that the condition will be abolished and the husband's leadership in choosing housing will return, while some have believed that the condition will continue. On the other hand, after the couple agreed and chose the house, the nature of this agreement, its provisions, and its effects have not been discussed. In this article, by accurately describing the legal relationships established between couples in each of the different assumptions and using various jurisprudential and legal sources and analyzing opinions and ideas and applying them to existing issues, it was concluded that a contract or condition that makes the choice of housing subject to the agreement of the couples is considered a condition or contract that must be fulfilled, which, like other contracts, must be implemented and requires its own specific performance guarantees. On the other hand, consent and choice of housing is also a binding contract and its dissolution requires rescission or termination by the couples.